DCC-2036 inhibits osteosarcoma via targeting HCK and the PI3K/AKT-mTORC1 axis to promote autophagy - Jun He; Liyang Yin; Qiong Yuan; Xiaotao Su; Yingying Shen; Zhongliang Deng (World Journal of Surgical Oncology)
Abstract Background Osteosarcoma is a common bone tumor in adolescents and children, characterized by rapid progression, high malignancy, poor prognosis, and a tendency for pulmonary metastasis. Despite extensive research efforts, the specific driver gene associated with osteosarcoma remains unidentified, underscoring the urgent need for novel therapeutic targets and targeted treatment options. Methods In vitro studies were conducted to assess the effects of DCC-2036 on the proliferation, migration, and invasion of osteosarcoma (OS) cell lines, employing cloning and Transwell experiments. Network pharmacological analysis, complemented by in vitro experimental validation, indicated the critical target responsible for the inhibitory effects of DCC-2036. RNA sequencing analysis demonstrated that DCC-2036 could induce autophagy in OS cells, with relative protein levels assessed using Western blotting following treatment with the autophagy inhibitor 3-MA and the mTOR agonist MHY1485. In vivo studies further confirmed the role of DCC-2036 in cell proliferation through subcutaneous tumorigenesis. Results In this study, we demonstrated that the small molecule tyrosine kinase inhibitor DCC-2036 effectively inhibited osteosarcoma (OS) cells in both cellular and animal models. We found that DCC-2036 significantly suppressed the proliferation of osteosarcoma cells and induced apoptosis; additionally, it notably inhibited cell migration, invasion, and epithelial-to-mesenchymal transition (EMT). HCK was identified as the key target mediating the effects of DCC-2036 on osteosarcoma. Mechanistically, DCC-2036 was shown to inhibit the expression of phosphorylated AKT (p-AKT), phosphorylated S6 kinase (p-S6K), and phosphorylated 4E-binding protein 1 (p-4EBP1) within the downstream PI3K/AKT/mTORC1 signaling pathway. Furthermore, in vivo experiments utilizing subcutaneous tumor xenografts in mice demonstrated that DCC-2036 effectively inhibited the growth of xenografted 143B cells in BALB/C-nude mice. Conclusions Collectively, these findings indicate that DCC-2036 promotes autophagy in osteosarcoma (OS) cells by targeting the HCK/AKT/mTORC1 axis and exerts anti-tumor effects without significant toxicity. Consequently, DCC-2036 emerges as a promising therapeutic agent for the treatment of HCK-overexpressing osteosarcoma.